The Anticipation of Schools Bullying - Eni Hidayati; Chistina Tri Cahyani; Desi Ariyana Rahayu; Muhammad Fatkhul Mubin; Tri Nurhidayati (University of Muhammadiyah Semarang, 2020)
Bullying is an action to harm other people that continuously happen either in groups or individually. Bullying could happen in a school environment to the students who are quiet, small and to those unable to defend themselves. This study aims to determine the anticipation of bullying in the school environment. The frequency distribution test results obtained that 250 teachers were in the sufficient category in anticipating bullying prevention and 3 teachers were still in the poor category. The research hopefully can stop bullying in the school environment. Bullying is an action to harm other people which is carried out continuously either in groups or individually. Bullying could occur in a school environment to students who are quiet, small and those unable to defend themselves. Bullying prevented by regulations that could be valid to all school members. The study aims to determine the anticipation of bullying in the school environment. The frequency distribution test results obtained that 250 teachers were in the sufficient category in anticipation of bullying prevention and 3 teachers were still in the poor category. The research hopefully can stop bullying in the school environment.